Local structure mapping of gel-spun ultrahigh-molecular-weight polyethylene fibers. (17th January 2022) - Huss-Hansen, Mathias K.; Hedlund, Erik G.; Davydok, Anton; Hansteen, Marie; Overdijk, Jildert; de Cremer, Gert; Roeffaers, Maarten; Knaapila, Matti; Balzano, Luigi
Abstract: We report on < 2 μm spatial resolution investigations of structural and morphological uniformity of aligned high-performance gel-spun ultrahigh-molecular-weight polyethylene (UHMWPE) fibers (thicknesses ranging from 60 μm to 300 μm) whose processing includes draw and quench. The degree of orientation of PE crystallites were found to increase near the surface of the fiber filaments (skin-core structure) in all samples when considering the P 2 orientation parameter calculated from wide-angle X-ray scattering (WAXS). The degree of orientation increases with drawn down ratio (keeping the quench temperature constant) and decreases with increasing quench temperature (keeping the draw down ratio constant). Orientation parameter values calculated from polarized Raman spectroscopy measurements of the symmetric C–C stretching (1130 cm −1 ) bond of PE showed clear skin-core structure in the samples with the highest overall orientation. We also employ small-angle X-ray scattering computed tomography (SAXS-CT) to show that the morphology (on the length scale of tens of nm) exhibit clear skin-core structure in two of the samples. The thickness of the skin region ( 12-17 µm) was estimated from the real-space SAXS morphology and found to be similar in undrawn and drawn filaments. Graphical abstract: Image 1 Highlights: High-resolution investigation of skin-core in UHWMPE filaments (diameters 60–300 μm). 2 > orientation parameter profiles from wide-angle X-ray scattering and Raman. Novel use of small-angle X-ray scattering computed tomography. 2D morphological maps of UHWMPE filament cross-sections with <2 μm spatial resolution.